The novel ProtekDuo ventricular assist device: Configurations, technical aspects, and present evidence. (July 2023) - Maybauer, Marc O; Koerner, Michael M; Swol, Justyna; El Banayosy, Aly; Maybauer, Dirk M
The ProtekDuo, single site dual lumen cannula can be used in a multitude of configurations. In the medical literature, the ProtekDuo is described as right ventricular assist device (RVAD), as left ventricular assist device (LVAD), as biventricular assist device (BiVAD) when combined with an Impella device or other LVAD's, as double lumen drainage cannula on cardiopulmonary bypass (CPB), as RVAD with oxygenator, in veno-pulmonary (V-P) ECMO configuration, venovenous-pulmonary (VV-P) ECMO configuration with additional drainage cannula, and in veno-venopulmonary (V-VP) ECMO configuration as double lumen return cannula. Improvements in flow and oxygenation have been recognized in various settings and need further scientific evaluation. We summarized the above-mentioned configurations, technical aspects, and the present literature available for the ProtekDuo.